FAKTOR-FAKTOR YANG MEMPENGARUHI KETERANDALAN PELAPORAN KEUANGAN DAERAH PROVINSI JAWA TIMUR - Ashrawiyadi, Irshani; Riharjo, Ikhsan Budi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is aimed to find out the influence of human resources quality, the use of information technology and the internal control to the Reliability of Financial Reporting with case study at Local Apparaturs Working Unit (SKPD) in East Java Province. This research is a quantitative research. The data collection method has been done by conducting survey. The data uses primary data which has been obtained by issuing questionnaires to the respondents. The sample collection technique has been done by using purposive sampling method. The numbers of samples are 96 respondents. Meanwhile, the analysis technique has been done by using multiple linear regressions analysis. The result of the research shows that the human resources quality, the use of information technology and the internal control give positive influence to the Reliability of Financial Reporting. The result of the research has supported all of the hypotheses which has been formulated in this research.Keywords: Human resources quality, the use of information technology, internal control, the reliability of financial reporting.